Kebutuhan Pengguna Perpustakaan Sekolah Luar Biasa Tunagrahita Santa Lusia Medan - melati imanuel sinaga (Jurnal Pustaka Nusantara dan Budaya, 2013)
Abstract The purpose of this research is toknow the needs of library users SLB-C Santa Lusia Medan. This research location in SLB-C Santa Lusia Medan Libbrary. The research method used is descriptive. Population and also sample in this research, are all the teacher SLB-C Santa Lusia Medan as the user with totaled 26 people. This research is done by giving the proposed procurement of books and journals to the respondent and also by observing the library collection. Result of this research indicate that the user needs cannot be net by the library SLB-C Santa Lusia Medan. It can be seen from the results of surveys that have been cunducted based on the proposed procurement of books and journals, the user very regarding the collection about the development psycology ABK (Children with Secial Needs), child psycology in general, treatment in autism children and learning methods for exceptional children. The refore, sould be additional purchases and collections to improve user knowledge, particularly in the treatment of children with special needs. This can be achieved if the user needs library is met accordance with their respective needs. Keywords: Needs User, library collection